ANALISIS PENGARUH KUALITAS SISTEMDANKUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA APLIKASI SISKEUDESDI KECAMATAN BRUNO KABUPATEN PURWOREJO - Misbah Misbah (STIE Rajawali Purworejo, 2023)
This research aims to determine the influence of system quality and information quality on user satisfaction of the Siskeudes application in Bruno District. The research design used in this research is a quantitative approach. The sampling used was using the Slovin formula. The error rate was 10% from 122 PPKD (Village Financial Management Implementers) spread across 18 villages in Bruno District so that a total of 54 respondents were obtained. The data used are primary data and secondary data with data collection techniques by conducting observations, interviews, distributing questionnaires, documentation and heritage studies. Hypothesis testing was carried out using analysis with the help of the SPSS version 23 application program. The results of hypothesis testing showed that partially there was a positive and significant influence between system quality on system user satisfaction, partially there was a positive and significant influence between information quality on system user satisfaction, simultaneously there was a positive and significant influence between system quality and information quality on satisfaction. siskeudes users. Keywords: ,